Pre‐interns: ready to perform?. (April 2015) - McKenzie, Susan; Burgess, Annette; Chapman, Renata; Mellis, Craig
Summary: Background: There is an expectation that interns can perform the core procedural skill of male catheterisation; however, it is unclear if our medical graduates are competent to do so, because there is no formal practical skills exit assessment in our current programme. Aim: We sought to investigate the level of experience, the self‐reported confidence, and measured competency of our pre‐intern (PRINT) students to perform the procedural skill of male catheterisation. Methods: We asked 100/147 (68%) PRINT students to complete a questionnaire to elucidate their experience and confidence prior to being practically assessed on a plastic manikin, using a faculty member validated 26–item checklist. Students were also invited to attend focus groups to help identify factors that had contributed to their practical performance. The lack of opportunity to perform the skill in the clinical setting had led to mediocre performance outcomes Results: Between 2010 and 2012, 100/147 (68%) PRINT students completed a questionnaire prior to being formatively assessed. The mean score for self‐reported confidence was 78.3/100 (95% CI 74.8–81.8), and the mean performance score was 85.6/100 (95% CI 83.2–87.9); however, the correlation coefficient between the confidence score and performance score was weak ( r = 0.18). Three focus groups were conducted, with a total of 12/100 (12%) students attending. Although students reported that they had sound knowledge of the skill, the lack of opportunity to perform the skill in the clinical setting had led to mediocre performance outcomes. Conclusion: We found no significant correlation among the level of experience, the self‐reported ability and actual performance when students were assessed under direct observation.